Analisis Kemampuan Literasi Membaca Permulaan Anak Usia 5-6 Tahun Di Kelompok Kerja Guru Renduwawo Kecamatan Aesesa Selatan Kabupaten Nagekeo - Dese, Mariana; Dhiu, Konstantinus Dua; Laksana, Dek Ngurah Laba; Oka, Gde Putu Arya (Jompa Research and Development, 2025)
The purpose of this study is to identify the level of early reading literacy ability in children aged 5 to 6 years who are in the teacher's working group in the Renduwuwo area, South Aesesa District, Nagekeo Regency. This study uses a descriptive approach with a qualitative method. The data collection techniques in this study include observation, interviews, and documentation. The tools used to collect data are in the form of observation guides, interview guides, and documentation of activities that are realized in the form of photos. The data analysis process refers to the Miles and Huberman interactive model, which consists of four stages, namely data collection, data reduction, data presentation, and conclusion drawn. The overall research results of early reading literacy skills in children aged 5–6 years are categorized as very good, with an average percentage of 84%. Children show optimal development in terms of understanding language, expressing language, and literacy, especially in the ability to recognize letter symbols, read their own names, and understand instructions and story content.